Answer: p(-3)=18
Step-by-step explanation:
To find p(-3), you plug -3 into p(x) and solve.
p(-3)=(-3)²-3(-3) [exponent]
p(-3)=9-3(-3) [multiply]
p(-3)=9+9 [add]
p(-3)=18
Now we found that p(-3)=18.
Answer:
might be 3
Step-by-step explanation:
Answer:
Solve for the first variable in one of the equations, then substitute the result into the other equation.
Point Form:
(−1/2,1/2)
Equation Form:
x=−1/2,y=1/2
Step-by-step explanation:
Answer:
11 and 22
Step-by-step explanation:
We can say that BC=2AC.
Since AB=33, AC=11 and BC=22.